Optimal biphase sequences with large linear complexity derived from sequences over Z4 - Udaya, Paramapalli; Siddiqi, Mohammad Umar (Institute of Electrical and Electronics Engineers Inc., 1996)
New families of biphase sequences of size 2T-1 + I, r being a positive integer, are derived from families of in- terleaved maximal-length sequences over 24 of period 2(Zr - 1). These sequences have applications in code-division spread- spectrum multiuser communication systems. The families satisfy Sidelnikov bound with equality on Omax, which denotes the maximum magnitude of the periodic crosscorreslation and out-of- phase antocorrelatiou values. One of the families satisfies Welch bound on Om,, with equality. The linear complexity and the period of all sequences are equal to T(T + 3)/2 and 2(2' - l), respectively, with an exception of the single m-sequence which has linear complexity r and period 2' - 1. Sequence imbalance and correlation distributions are also computed.